Effect of Hemoglobin Levels on the Process of Healing Post Sectio Caesarea Wounds - setiawan, Danis; Wulandari, Ning Arti; Arsa, Sandi Alfa Wega (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
The long healing of post sectio caesarea wounds has an impact on patients and their families.In addition to the additional burdensome costs, patients can experience trauma due to the wound healing process that lasts a long time.Hemoglobin is the main component that transports oxygen and nutrients needed for the wound healing process. This study aims to analyze the effect of hemoglobin levels on the healing process of post sectio caesarea wounds at Aminah Hospital Blitar.The research design uses a case control approach samples were taken using consecutive sampling techniques with research inclusion criteria of 89 respondents.Data on hemoglobin levels were taken from secondary data on preoperative hemoglobin levels of patients in medical record documents and data on the process of wound healing seen from the results of one-time observation when the patient controls the obstetric polyclinic between day 7 to day 10 post sectio caesarea.Data were analyzed using a simple linear regression test. The results showed that 62.9% of respondents had normal hemoglobin levels and 79.77% of respondents showed good wound healing processes.The results of the statistical test analysis showed a p value of 0.000 which was smaller than α of 0.05 with an R-square of 0.196.This means that there is an effect of hemoglobin levels on the wound healing process post sectio caesarea.So it is expected that pregnant women and their families pay attention to the value of hemoglobin levels during pregnancy and after delivery to ensure health and wound healing post sectio caesarea.Keywords:hemoglobin,wound,post sectio caesarea